Nanoparticles and Nanoliposomes for Hair Growth Serum - Arismunandar, Arif; Chabib, Lutfi; Ramadani, Arba Pramundita; Suryani, Arman; Kamarulzaman, Ezatul Ezleen (CHEESA: Chemical Engineering Research Articles, 2024)
Solubility in penetrating the follicles is the main obstacle in the formulation of hair growth serum preparation with chemicals derived from natural or synthetic materials. Therefore, a delivery system is needed to deliver more chemical compounds into the follicles. Nanoparticles and nanoliposomes are potential chemical compound delivery systems in hair growth serum. Specifically, nanoparticles with a particle size of less than 200 nm can increase the transport of serum chemical compounds into the scalp. The small particle size makes the interaction between atoms and molecules faster and prevents clumping with the repulsive force of dispersed particles. Meanwhile, nanoliposomes with lipids as encapsulation in the delivery of lipophilic or hydrophilic chemical compounds with nanosizes can significantly increase serum diffusion on the scalp.